(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
Potash ore beneficiation is a crucial process in the extraction and purification of potassium compounds, particularly potassium chloride (KCl), which is vital for fertilizer production. The beneficiation of potash ores, primarily composed of silvinite (KCl + NaCl), requires a systematic approach to separate the valuable sylvite from associated gangue minerals, primarily halite. This thesis presents a comprehensive overview of the sequential stages involved in potash ore beneficiation, including crushing and grinding, desliming, flotation, dewatering, and drying. Each stage is optimized based on ore mineralogy, particle size distribution, reagent chemistry, and environmental conditions. Emphasis is placed on flotation, the most efficient separation method, along with supportive techniques such as selective crystallization and brine recycling. The thesis also explores advancements in process automation and control technologies. The outlined beneficiation stages provide a framework for enhancing recovery, improving product purity, and reducing environmental impact in potash processing operations.